At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
- f⁻¹(x) = (x + 1) / (x - 2)
- f⁻¹(1 ) = - 2
Step-by-step explanation:
Given function:
- f(x) = (2x + 1) / (x - 1)
Find its inverse, substitute x with y and f(x) with x, solve for y:
- x = (2y + 1) / (y - 1)
- x(y - 1) = 2y + 1
- xy - x = 2y + 1
- xy - 2y = x + 1
- y(x - 2) = x + 1
- y = (x + 1) / (x - 2)
Substitute y with f⁻¹(x):
- f⁻¹(x) = (x + 1) / (x - 2)
Find f⁻¹(1 ):
- f⁻¹(1 ) = ( 1 + 1) / (1 - 2) = 2 / - 1 = - 2
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.